Power and program planning in a community-based context - Sue M. Scott; Margo, Schmitt-Boshnick; Shelley Lester (Adult Education Research Conference, 1995)
Recent theorizing in program planning focuses on the critical perspective which examines contextual factors and power relationships. The research question here asks, to what extent do power relationships affect the program planning process in Candora, a community-based organization?